A rare cardiac complication of left-sided tunneled hemodialysis catheter insertion - Mythri Shankar; Nishanth Khandenahallipalya Ravindranath; Nagaraja Moorthy; H V Jayanth Kumar (Wolters Kluwer Medknow Publications, 2023)
Left atrial perforation during central venous catheter insertion is an extremely rare complication which can have catastrophic outcomes if left unrecognized. We describe a rare case of the left atrial catheter malposition during tunneled hemodialysis catheter insertion from the left internal jugular vein, which was managed successfully by surgical reposition and simultaneously vascular access was secured by salvaging the same catheter in a patient with poor arteriovenous anatomy for surgical arteriovenous fistula.